AC/DC converter for DC traction power supply system with high-speed train operation - Sokol, Yevgen I.; Sychenko, Viktor; Voitovych, Yurii; Kosariev, Yevhen; Styslo, Bohdan; Hubskyi, Petro (My University, 2019)
Purpose of the work is improved approaches to ensure the required quality parameters of voltage in the traction network based on modern technologies and equipment. The pulsating mode of the power consumption in the railroad power supply network is the cause of the occurrence of voltage pulsations in the contact network. The use of active rectifiers in the electric power supply system of the railroad is proposed. The control system is developed by the converter, which allows to stabilize the output voltage in the DC link and also provides the unit power factor consumed by the converter and the THD consumption current at the level of 8%. A mathematical model of the converter was developed and a study of its main modes of operation was performed.
Keywords: AC/DC converter; power quality; traction power supply system; voltage quality; traction network force; operation modes; power fluctuation; THD